2020
DOI: 10.24198/pjdrs.v4i2.27506
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efek konsumsi kopi arabika selama masa laktasi pada tikus Wistar terhadap erupsi gigi anak tikus</p><p>The effect of Arabica coffee consumption during lactation of breastfeeding Wistar rats on the tooth eruption of the offsprings</p>

Abstract: Efek konsumsi kopi arabika selama masa laktasi pada tikus Wistar terhadap erupsi gigi anak tikus (Choirunnisa, dkk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This finding is consistent with that of Choirunnisa which states that caffeine consumption of more than 300 mg per day can inhibit the eruption process of rat cubs' teeth. 10 Caffeine consumption may cause diuresis, a condition where there is an increase in the volume of urine secreted by the body as well as the amount of loss of substances dissolved in water that fail to be reabsorbed in the renal tubules. One of these substances is calcium, an essential nutrient for the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with that of Choirunnisa which states that caffeine consumption of more than 300 mg per day can inhibit the eruption process of rat cubs' teeth. 10 Caffeine consumption may cause diuresis, a condition where there is an increase in the volume of urine secreted by the body as well as the amount of loss of substances dissolved in water that fail to be reabsorbed in the renal tubules. One of these substances is calcium, an essential nutrient for the body.…”
Section: Discussionmentioning
confidence: 99%
“…Choirunnisa showed that consumption of Arabica coffee of 2.7 grams/200 gram body weight/day during lactation period affected the eruption of rat cub's teeth. 10 Other researchers also found that consuming Arabica coffee with an excess dose of 2.7 grams/200 grams body weight/day during lactation can reduce the density of the mandibular bones of Wistar rat cubs. 11 Considering these findings and limited references and research on radiographic images of calcified teeth of rat cubs, we seek to conduct an experimental study on the effect of Arabica coffee consumption during lactation on Wistar rats on radiographic images of calcified teeth of rat cubs.…”
Section: Introductionmentioning
confidence: 95%